Tuesday

July 22, 2014

July 22, 2014

Posted by **Anonymous** on Saturday, March 12, 2011 at 9:00am.

- trig -
**MathMate**, Saturday, March 12, 2011 at 9:24am(sin^4x-cos^4x)/(sinx-cosx)

=(sin^2x+cos^2x)(sin^2x-cos^2x)/(sinx-cosx)

=1*(sinx+cosx)(sinx-cosx)/(sinx-cosx)

=sinx+cosx

**Related Questions**

Trig........ - I need to prove that the following is true. Thanks (cosx / 1-sinx...

Trigonometry. - ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! ...

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

Trig - prove the identity (sinX)^6 +(cosX)^6= 1 - 3(sinX)^2 (cosX)^2 sinX^6= ...

Trigonometry - Prove the following trigonometric identities. please give a ...

Math - Pre- Clac - Prove that each of these equations is an identity. A) (1 + ...

Trigonometry Check - Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [...

trig - I need to prove equality. a) (sina + cosa)^2 -1 / ctga - sinacosa = 2tg^...

Trig....... - I need to prove that the following is true. Thanks (2tanx /1-tan^x...

trig - express this in sinx (1/ cscx + cotx )+ (1/cscx- cotx) i got 2sinx is ...